PENGARUH INFLASI DAN SUKU BUNGA TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI INDONESIA (PERIODE 2015-2019) - Sanusi, Masitoh, Hamdanah; Nuryati (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2023)
This study aims to determine what factors affect stock prices, especially the Composite Stock Price Index (IHSG). There are so many macroeconomic factors or variables that can affect stock prices, such as inflation, interest rates, the exchange rate of the Rupiah currency against dollar, GDP and many more. In this study, the factors taken by the researcher are the inflation rate and the interest rate. In other words, this study focuses on the effect of inflation and interest rates on the Composite Stock Price Index (IHSG). Therefore, in this study, the determining variables or independent variables are the inflation rate and interest rates, while the Composite Stock Price Index (IHSG) acts as the dependent variable. In the scope of this study, data from inflation, interest rates and the Composite Stock Price Index (IHSG) are monthly data for the 2011-2015 period, respectively, which are taken from statistical data from the official websites of Bank Indonesia (BI), the Indonesia Stock Exchange (IDX) and Central Bureau of Statistics (BPS). This type of research is an empirical study and the data was obtained by documentation method from secondary data. In this study, data processing and analysis techniques used multiple regression analysis and panel analysis. Tests were carried out using the F test, T test, and also the R Square test. From these tests, it shows that inflation has no effect on the Composite Stock Price Index (IHSG), while interest rates have an effect on the Composite Stock Price Index (IHSG